Transforming Fashion Marketing with AI : Possibilities of Artificial Intelligence in Shaping Brand Perception and Consumer Trust - Gawinski, Jan-Michel; Machek, Martin; Kolouchová, Daniela; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This thesis investigates the transformative character of artificial intelligence (AI) in the field of fashion marketing. The main goal of the research is to understand the possibilities of AI in shaping brand perception and consumer trust. The theoretical framework is based on marketing AI technologies, the fashion industry, brand perception and consumer trust, and the challenges and ethical considerations when using AI. A qualitative research approach, including semi-structured in-depth interviews with industry experts, constitutes the primary data collection method. The results of the data analysis are presented and discussed, and recommendations to fashion companies and their marketing departments are given. The results of this study indicate that AI has a transformative character and can shape brand perception and consumer trust in fashion marketing by precisely implementing AI-enabled applications in the brand funnel. However, aligning AI integrations with brand strategy and positioning is crucial to achieving the desired positive effects.
Vedoucí práce: Martin Machek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses